2021
DOI: 10.1111/joa.13568
|View full text |Cite
|
Sign up to set email alerts
|

Sexual dimorphism in the bed nucleus of the stria terminalis, medial preoptic area and suprachiasmatic nucleus in male and female tree shrews

Abstract: Sex differences in behaviour partly arise from the sexual dimorphism of brain anatomy between males and females. However, the sexual dimorphism of the tree shrew brain is unclear. In the present study, we examined the detailed distribution of vasoactive intestinal polypeptide‐immunoreactive (VIP‐ir) neurons and fibres in the suprachiasmatic nucleus (SCN) and VIP‐ir fibres in the bed nucleus of the stria terminalis (BST) of male and female tree shrews. The overall volume of the SCN in male tree shrews was compa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 81 publications
0
2
0
Order By: Relevance
“…Consistent with this, VIP innervations from the DR-PAG region to the BNST, which was not specified as DAT+/VGlut2+, have been reported in several studies ( Petit et al, 1995 ; Kozicz et al, 1998 ). This VIP signal in the BNST exhibits sexual dimorphism in humans, finches, and tree shrews ( Zhou et al, 1995 ; Chung et al, 2002 ; Goodson et al, 2006 ; Ni et al, 2022 ). Yu et al (2021) reported that the manipulation of DA DR-PAG neuronal activities induced different behavioral modulations between male and female mice, which might be because of the sexual dimorphism of VIP fibers in BNST, originating from the VIP subpopulation of DA DR-PAG neurons.…”
Section: Discussionmentioning
confidence: 99%
“…Consistent with this, VIP innervations from the DR-PAG region to the BNST, which was not specified as DAT+/VGlut2+, have been reported in several studies ( Petit et al, 1995 ; Kozicz et al, 1998 ). This VIP signal in the BNST exhibits sexual dimorphism in humans, finches, and tree shrews ( Zhou et al, 1995 ; Chung et al, 2002 ; Goodson et al, 2006 ; Ni et al, 2022 ). Yu et al (2021) reported that the manipulation of DA DR-PAG neuronal activities induced different behavioral modulations between male and female mice, which might be because of the sexual dimorphism of VIP fibers in BNST, originating from the VIP subpopulation of DA DR-PAG neurons.…”
Section: Discussionmentioning
confidence: 99%
“…22 Because VP release from SCN neurons is activity dependent, 19,20 these observations suggested there might be differences in the firing pattern of SCN VP neurons in the two sexes. Indeed, sexually dimorphic features of the SCN have been reported in several species, [28][29][30][31][32][33][34] including humans, 35 and sex differences in circadian physiology are well documented. [35][36][37][38][39][40] Therefore, the goal of this study was to characterize and compare the circadian profiles of electrical activity in identified SCN VP neurons of male and female rats.…”
Section: Discussionmentioning
confidence: 99%